High follicle‐stimulating hormone levels accelerate cartilage damage of knee osteoarthritis in postmenopausal women through the PI3K/AKT/NF‐κB pathway. Issue 10 (21st September 2020) - Liu, Yaping; Zhang, Mengqi; Kong, Dehuan; Wang, Yan; Li, Jian; Liu, Wenjuan; Fu, Yilin; Xu, Jin
Abstract : Osteoarthritis is the main cause of pain and disability in the elderly, with the most commonly affected joint being the knee. The prevalence of knee osteoarthritis (KOA) is significantly increased in postmenopausal women, although the mechanisms underlying KOA remain unclear. The present study aimed to investigate the association between follicle‐stimulating hormone (FSH) and postmenopausal women with KOA aged between 50 and > 70 years, as well as explore its underlying molecular mechanisms. Here, we report that the 50–60 years age group had the highest level of serum FSH. Compared to the low FSH group (< 40 mIU·mL −1 ) in the same age group, the high FSH group (> 40 mIU·mL −1 ) showed more severe cartilage damage. Furthermore, phosphorylated (p)‐phosphoinositide 3‐kinase (PI3K)/PI3K, p‐AKT/AKT and p‐nuclear factor kappa B (NF‐κB)/NF‐κB levels were significantly higher in the high FSH group compared to the low FSH group. Immunofluorescence experiments showed that FSH stimulation promoted the translocation of NF‐κB p65 into the nucleus, and decreased type II collagen and aggrecan in ATDC5 cells. Moreover, we used western blotting in ATDC5 cells to demonstrate that FSH decreased type II collagen and increased p‐PI3K/PI3K, p‐AKT/AKT, p‐NF‐κB/NF‐κB and p‐IKB/IKB in a concentration‐dependent manner. Our results suggest that increased FSH levels are associated with KOA for postmenopausal women aged 50–60 years and that high FSH levels might damage the cartilage tissues through the PI3K/AKT/NF‐κB pathway. Abstract : Knee osteoarthritis (KOA) is prevalent in postmenopausal women and a cause of pain and disability in elderly populations. Here, we report high follicle‐stimulating hormone (FSH) levels across postmenopausal female KOA patients aged 50–60 years. We speculate FSH might damage cartilage tissues through the phosphoinositide 3‐kinase/AKT/nuclear factor kappa B pathway. Our findings suggest that FSH modulation holds promise as a novel treatment for postmenopausal female KOA patients aged 50–60 years.